A displacement based seismic design procedure for RC buildings and comparison with EC8. - Panagiotakos, T.B (Earthquake engineering & structural dynamics.)
A procedure for displacement based seismic design (DBD) of reinforced concrete buildings is described and applied to a 4 storey test structure. The essential elements of the design procedure are : (a) proportioning of members for gravity loads; (b) estimation of peak inelastic member deformation demands in the so-designed structure due to the design ('life-safety') earthquake; (c) revision of reinforcement and final detailing of members to meet these inelastic deformation demands; (d) capacity design of members and joints in shear. Additional but non-essential steps between (a) and (b) are : (i) proportioning of members for the ULS against lateral loads, such as wind or a serviceability ('immediate occupancy') earthquake; and (ii) capacity design of columns in flexure at joints. Inelastic deformation demands in step (b) are estimated from an elastic analysis using secant to yield member stiffnesses. Empirical expressions for the deformation capacity of RC elements are used for the final proportioning of elements to meet the inelastic deformation demands. The procedure is applied to one side of a 4 storey test structure that includes a coupled wall and a two bay frame. The other side is designed and detailed according to Eurocode 8. Major differences result in the reinforcement of the two sides, with significant savings on the DBD side. Pre-test calculations show no major difference in the seismic performance of the two sides of the test structure.